Expression patterns of pathogenicity genes during Phytophthora pisi infection of pea roots - Hosseini, Sara (SLU/Dept. of Forest Mycology and Plant Pathology, 2010)

(untitled)
The genus Phytophthora (phylum Oomycota), contains destructive plant pathogens that cause enormous economic damage to many important crop species. These fungus-like microorganisms employ diverse mechanisms to break down plant defences. Understanding of the strategies by which these pathogens colonize their host is essential to establish improved methods for controlling Phytophthora infection. P. pisi is a new species of Phytophthora that causes root rot in pea and is a putatively devastating pathogen for cultivation of pea in many parts of the world. Furthermore, like other species of oomycetes such as P. infestans and P. sojae this species can be used as a model in molecular plant-microbe interactions research. This study was planned to provide an insight into the transcriptome of P.pisi during the infection process of pea roots and also on necrotic material. Thus, pea roots were inoculated with P. pisi and then harvested at six different time points. Colonization levels of P. pisi in pea roots as well as the expression of genes possibly involved in the infection process were monitored using different DNA-based methods (quantitative PCR and (RT)-PCR). Ten candidate pathogenicity genes were identified and sequenced for P. pisi and their expression was measured during the infection process using quantitative reverse transcription (RT)-PCR. The putative pathogenicity genes cystein protease (Pro1), putative endo 1,3; 1,4 beta glucanase (Glu1), phosphoenolpyrovate carboxykinase (Pck1), enzyme inhibitors (Gip1) and (Epi1), crinkler-like protein (Crn1) and putative ABC-transporter (Pdr1), were expressed during infection. Transcript levels of Pro1, Glu1, Pdr1 and Crn1 increased over the experimental period, while transcript profiles of Gip1 and Epi1 showed high expression during the first 2-6 hours following inoculation. No expression was detected for pyruvate dehydrogenase (Pdh1), or the putative effector genes Avr1b-1 or Nip1. In a follow-up experiment, Pro1 expression was higher during P. pisi growth on dead pea roots at 20 hours post-inoculation when compared with growth on living roots. Epi1 was only expressed on live host material. Domain structure analysis revealed that P. pisi Pro1 protease contains three conserved domains, a peptidase domain, an inhibitor domain and a lipid binding domain. Phylogenetic analysis of P. pisi protease revealed that this protein is most closely related to a homologue from P. sojae and likely belongs to a cathepsin-L-like group from the C1A subfamily of peptidases.